COMPARISON OF FREQUENCY OF POST OPERATIVE SENSITIVITY IN AMALGAM RESTORATIONS USING COPAL VARNISH AND DENTIN ADHESIVE LINER - Saba, Kiran; Maxood, Anser; Abdullah, Saeeda; Riaz, Amna; Din, Shahab ud (Journal of Ayub Medical College Abbottabad, 2018)
Background: Micro leakage around the margins of a restoration is believed to be one of the main causes of postoperative sensitivity. Dental amalgam is a non-insulating material and has the potential to transfer heat and cold causing irritation of the pulp. Different dentin tubule sealers are used under amalgam restoration to compensate for this post-operative sensitivity. This study was conducted to compare the frequency of sensitivity in amalgam restorations using copal varnish and dentin adhesive liner (dentin bonding agent). Methods: A total of 60 patients of either gender, aged 18-40 years having class 1 carries in posterior teeth were included. Teeth with restorations, dentinal sensitivity and patients taking analgesic drugs for chronic pain conditions were excluded. The selected patients were placed randomly into Group A (copal varnish) & Group B (dentin adhesive liner), by using computer generated table of random numbers. Restored teeth were evaluated 1-month post operatively for sensitivity. Results: Mean age was 25.63±5.42 years. Out of 60 patients, 68.0% were females and 32.0% were males with a female to male ratio of 2:1. The mean post-operative pain score was 2.83±2.79 in Group A and in Group B, it was 1.43±2.14 with a p-value of 0.03. There was no pain on application of a cold stimulus in 14 (46.7%) patients in Group A (copal varnish) while in Group B (Dentin adhesive), no pain was seen in 23 (76.7%) patients with p-value of 0.02. Conclusion: This study concluded that dentin adhesive liner (dentin bonding agent) is better than copal varnish in reducing postoperative sensitivity in amalgam restorations. Keywords: dental caries; amalgam; microleakage; dentin adhesive liner; copal varnish; postoperative sensitivity